Land Use in the Southern Cone from the Mid-Nineteenth Century to 1950 - Secreto, María Verónica (2024)
This chapter analyzes the genesis of legal and agronomic “modernity” in a territory that generally had low density human occupation and exploitation during the colo- nial period until the middle of the twentieth century. The chapter discusses the role of the state, the private sector, and Indigenous groups, differentiating the forms of land use in relation to productive activities in the subregions. It should be noted that the period under study coincides with the fall of the colonial empires (Spanish and Portuguese) and the birth and consolidation of the nation states. For this reason, the chapter focuses on explaining the modalities in which a system of exploitation was established in four countries: Chile, Argentina, Uruguay and Brazil.